2016
DOI: 10.1038/srep28462
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 metabolism of the post-lanosterol intermediates explains enigmas of cholesterol synthesis

Abstract: Cholesterol synthesis is among the oldest metabolic pathways, consisting of the Bloch and Kandutch-Russell branches. Following lanosterol, sterols of both branches are proposed to be dedicated to cholesterol. We challenge this dogma by mathematical modeling and with experimental evidence. It was not possible to explain the sterol profile of testis in cAMP responsive element modulator tau (Crem τ) knockout mice with mathematical models based on textbook pathways of cholesterol synthesis. Our model differs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…7c) were recently proposed as strong RORC agonists11. Elevated levels of lathosterol and 7-dehydrocholesterol might support the existence of a shunt pathway, as previously proposed by us2223 and others24.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…7c) were recently proposed as strong RORC agonists11. Elevated levels of lathosterol and 7-dehydrocholesterol might support the existence of a shunt pathway, as previously proposed by us2223 and others24.…”
Section: Resultssupporting
confidence: 53%
“…Hepatic cholesterol intermediates (including LAN) generally correlate with their plasma concentration, but not in the case of DHL24. This suggested that DHL might be metabolized in a shunt pathway as most recently confirmed by us39, or might be exported to the bile, which still awaits experimental confirmation. The former option is enticing as it offers an explanation as to why we found no decrease in sterol intermediates immediately before their conversion to cholesterol in H Cyp51 −/− mice (e.g.…”
Section: Discussionmentioning
confidence: 87%
“…Doing the most relevant experiments has not been possible with P450 11A1, in that the only types of labeling experiments possible with the substrate cholesterol are described here and the ability to catalyze other reactions is limited. 27 P450 11A1 does catalyze a number of other reactions, particularly with vitamin D, 42,43 but none of these involve the formation of carbonyls. Reactions with other P450s can be considered, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Putatively, 5′a could be oxidized in one of the methyl groups to generate a diol intermediate (5′c), which could then lose a single carbon unit by the C-C bond cleavage during further oxidation, generating 2′b and a molecule of formaldehyde. This mechanism is not uncommon in the reactions of cholesterol side chain cleavage (39,40). For example, the transformation from cholesterol to pregnenolone depends on the cleavage of C20,C22 carbon-carbon bond catalyzed by CYP11A1 (41).…”
Section: Selective Oxidation Of Diverse Alkylphenols By the Chemomimeticmentioning
confidence: 95%